(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2018)
Four non-woods such as, dhaincha (Sesbania bispinosa), jute stick (Corchorus capsularis), wheat straw (Triticum aestivum) and corn stalks (Zea mays) were cooked by potassium hydroxide (KOH) at the optimum conditions of soda pulping. Dhaincha, wheat straw and corn stalks were delignified to kappa number 19.4, 13.6 and 19, respectively, while jute stick was not delignified sufficiently (kappa number 32.5). All these four raw materials maintained good yield in KOH process. Dhaincha produced the highest pulp yield (50.5%) and wheat straw had the lowest pulp yield (44.7). All pulps were bleached by D0EpD1 bleaching sequences in identical bleaching conditions. Final pulp brightness reached to above 80% ISO except jute stick pulp. Jute stick pulp reached to 74.9% brightness only after the consumption of 30 kg ClO2/ ton of pulp. The overall bleaching yields were 92.6%, 88.4%, 90.1 and 90.8% for dhaincha, jute stick, wheat straw and corn stalks pulps, respectively. The oSR of these four non-wood bleached pulps was above 20, consequently improved papermaking in the unrefined state. Beating rapidly increased papermaking properties, as for example, the tensile index of dhaincha pulps increased from 49 N.m/g in the unrefined pulp to 90 N.m/g in the beaten 50 oSR. It can be seen that KOH is a good substitute to soda process for non-wood. Bangladesh J. Sci. Ind. Res.53(1), 1-6, 2018